Catalytic Asymmetric Hydrogenation of Dehydroamino Acid Esters with Biscarbamate Protection and Its Application to the Synthesis of xCT Inhibitors. Issue 20 (15th March 2019) - Yasuno, Yoko; Mizutani, Iho; Sueuchi, Yuki; Wakabayashi, Yuuka; Yasuo, Nozomi; Shimamoto, Keiko; Shinada, Tetsuro
Abstract: Invited for the cover of this issue is Tetsuro Shinada and co‐workers at Osaka City University and Suntory Foundation For Life Science. The image depicts new catalytic asymmetric synthesis (dragon ball), designed molecules (dragon), and the molecular target (xCT) on cancer cells (tiger). Read the full text of the article at 10.1002/chem.201900289 . Abstract : " This work includes two challenges: the development of new catalytic asymmetric synthesis of chiral amino acids and novel xCT inhibitors based on an original molecular design ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 5145 ff. (DOI:10.1002/chem.201900289 ).